PENGARUH SELF-ESTEEM, KEPERCAYAAN, DAN NARSISME TERHADAP PERILAKU INDIVIDU DALAM BERBAGI PENGETAHUAN DI FACEBOOK - , Afitra Kuntum Rahma Ari Prawita ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was aimed to measure the effect of self-esteem, trust, and narcissism as well as to analyze gender and education background effect on individual behavior during knowledge sharing in Facebook as control variable. This research was focused on individual level behavior-affecting factors during knowledge sharing. Subjects were 98 bank worker respondents listed in researcherâs Facebook account friend list. Results showed that self-esteem gave significantly positive impact on individual behavior during knowledge sharing in Facebook. Measurement on trust effect was showed as significantly affected knowledge sharing. Finally, multiple regression analysis showed that narcissism was not significantly affecting it.